2013
DOI: 10.1002/hed.23273
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of incidentally discovered thyroid nodules referred to a high‐volume head and neck surgeon

Abstract: Based on radiologic findings, risk factors, and FNA results, many incidental thyroid nodules can be observed. Incidental thyroid nodules should be evaluated in the same fashion as a palpable thyroid nodule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
4
19
3
Order By: Relevance
“…Men were significantly more likely to be diagnosed incidentally than women in our study; however, about 78% of patients with incidental thyroid nodules were women. This is consistent with other studies that reported about 70% of their patients with incidental thyroid nodules were women …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Men were significantly more likely to be diagnosed incidentally than women in our study; however, about 78% of patients with incidental thyroid nodules were women. This is consistent with other studies that reported about 70% of their patients with incidental thyroid nodules were women …”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, training detected 3% of the incidental thyroid nodules, which is likely unique to a teaching hospital. This distribution of indications for imaging differs from Kroeker et al, who reported that thyroid dysfunction (21%), neck discomfort (18%), and a lateral neck mass (14%) were the most common indications.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…8,9 Of patients who undergo FNAB, 22%-51% proceed to surgery. [10][11][12] These surgical patients represent an important group to study because they have higher costs and morbidity associated with the work-up of their ITNs. Thus, it is important to consider the costs and benefits of work-up in patients with ITN who fall into this surgical group.…”
mentioning
confidence: 99%
“…Part of the reason may be due to an increase in the detection rates of ITD during examinations. In addition, ITD may be diagnosed during surgery or during a final histopathological examination for head and neck surgery [5].…”
mentioning
confidence: 99%